2009
DOI: 10.3144/expresspolymlett.2009.95
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the electrical properties of the carbon nanotube/polymer composites

Abstract: Abstract. In this paper, pristine and oxidized multi-walled carbon nanotube (MWCNT)/poly(vinylidene fluoride) (PVDF) composites were prepared and the temperature dependence of some electrical properties of these composites were studied. It is found that the transition temperature (Tt), from positive temperature coefficient (PTC) to negative temperature coefficient (NTC) effect, of the oxidized MWCNT/PVDF composites shifted to a higher temperature. The shift of the Tt of the oxidized MWCNT/PVDF composites can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 25 publications
6
39
0
Order By: Relevance
“…This behavior has been explained by the rearrangement of the percolated network that results in an increased number of interconnections. Alternatively, the increasing thermal energy may facilitate a conduction potential barrier jump [18]. PC is a polymer with T g = 420 K; the NTC behavior of CNT/PC observed in our experiments is thus consistent with the literature.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 90%
See 1 more Smart Citation
“…This behavior has been explained by the rearrangement of the percolated network that results in an increased number of interconnections. Alternatively, the increasing thermal energy may facilitate a conduction potential barrier jump [18]. PC is a polymer with T g = 420 K; the NTC behavior of CNT/PC observed in our experiments is thus consistent with the literature.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 90%
“…It is accepted that the main mechanism leading to resistance change with temperature is the modification of the tunneling distance caused by a mismatch in the coefficients of thermal expansion among the constituents [17,18,19,20]. The results for our M A N U S C R I P T…”
Section: Temperature-dependent Resistance Changementioning
confidence: 55%
“…Moreover, in semicrystalline polymers, the volume expansion of the polymer matrix which separates the fillers is also attributed to the transformation of the crystalline phase to the amorphous phase. These results agree with others reported in the literature [50]. For instance Tao et al [51] also reported a decrease in conductivity with temperature for a composite of MWCNTs and polyethylene at higher temperatures (T > T m ) and was related to the phenomena of crystallization of polyethylene which would disconnect the conductive paths [51].…”
Section: Pani Systemsupporting
confidence: 83%
“…Other authors [40,52] also observed a continuous increase of conductivity with temperature below T m (positive temperature coefficient effect of the resistivity). Moreover, an effect similar was reported by Li et al [50] below a transition temperature of 80°C. This effect was explained by the fact that at higher temperatures (T > T m ), Brownian motion of the carbon nanotubes make them mobile within the melting matrix and they tend to coagulate which results in an decrease of the electrical conductivity of the composite with temperature.…”
Section: Pani Systemsupporting
confidence: 73%
“…The dielectric constant increases again. 39 There are two mechanisms of electrical conduction. One is when the conductors in composites connect with each other to form conductive routes, and the other is that the conductors in composites do not connect with each other, but their distances are so small that the electrons can be transmitted through electron tunnels formed among conductors nearby.…”
Section: Scanning Electron Microscope Analysismentioning
confidence: 99%